(untitled) (Scientific journal of the Fergana State University, 2024)
This article examines the theoretical and methodological foundations for the development of knowledge on sports aesthetics among future physical education teachers, a practical methodological system for the development of knowledge on sports aesthetics, and the effectiveness of the development of knowledge on sports aesthetics. The physical culture content of the development of knowledge of future physical education teachers on the aesthetics of sports is also analyzed.